A study of urinary tract infection in children aged 1-5 years admitted with acute febrile illness - Sohail, Abdus Subhan; K., Pushpalatha; S., Uday Kumar; Kumar, Kushal (International Journal of Contemporary Pediatrics, 2023)
Background: Urinary tract infection (UTI) is a common problem in pediatric age group and is a significant risk factor for long term sequelae. The clinical signs and symptoms of UTI are nonspecific in the first 5 years of age. Methods: A cross-sectional study was conducted after obtaining institutional ethical clearance and informed consent from the parents, on 350 children aged 1 to 5 years admitted in with acute febrile illness. Results: Out of 350 children with acute febrile illness 23 had culture proved UTI. The frequency of occurrence of UTI was 6.5%. Majority 8 (34.7%) of children with UTI were between 1-2 yrs. There was female preponderance with male: female ratio of 1:2.3. Twelve children with UTI belonged to lower socioeconomic status. Fourteen (60.87%) had nonspecific symptoms. Seventeen (73.9%) children had a provisional diagnosis other than UTI. pyuria >10 WBC/HPF had higher specificity (98.5%) and positive predictive value (72.2%) than >5WBC/HPF. Combined bacteruria and pyuria had specificity of 98.8 %. The most common organism isolated from children with UTI was E. coli, most of the organisms (73.9%) were sensitive to ceftriaxone. Abnormal ultrasonographic features was found in 17.4 % of children with UTI. Conclusions: As the febrile children with UTI usually present with nonspecific signs and symptoms, urine culture should be considered as a part of diagnostic evaluation. Urine culture is the gold standard for diagnosis of UTI. However combined bacteruria and pyuria had specificity of 98.8% and can be used to start empirical antibiotic therapy awaiting culture reports.